Why Study Journalism: Motivation of Future Kazakh Journalists - Brown, M; Ibrayeva, G (Farabi Journal of Social Sciences, 2019)
This paper is part of a large international research project: Journalism Students across the Globe: Professionalization, Identity and Challenges in a Changing Environment. Journalism education in Kazakhstan, like elsewhere, needs to account for changes in the information environment. This project examines the motives to study journalism by students from Kazakhstan. Do today’s student motivations reflect an understanding of new media with its text, images, infographics, data, and new genres; and how should a journalist combine knowledge of the various media fields? Study of the motivations of Kazakh students in this context is important for both national interests and aligning Kazakh journalism education with international expectations. An online survey used open-ended questions to elicit replies. Questions focused on career opportunities for journalism students, aspects of education that motivate students and whether a university degree is necessary to become a professional journalist. Findings were compared to historical journalistic motivations in Kazakhstan. Students now are driven by different motives. In the past journalistic education was a building block for a career in politics or writing. Now students know various fields of journalism and what the fields offer. Journalism students prefer TV, but a high percentage also prefer the increasingly important online environment. The formula for modern education in the age of information and new technologies is an ongoing systematic process of learning for both educators and students, driven by motivations that are important not only within the walls of universities, but in everyday life. Key words: journalism education, motivation, new media, state independence, Kazakhstan.